Comparative analysis of CNN coverage of weather-related disasters in USA, Japan, and India. Issue 1 (2nd January 2021) - Gyamfi, Prince Adu
Abstract : Previous research studies have investigated news media coverage of weather-related disasters. However, little is known about how CNN, a broadcast enterprise with global reach, has covered and framed weather disasters happening in a Western country and an Asian country. Thus, the present study used a qualitative method to analyze how CNN covered and framed weather-related disasters in the USA, Japan, and India. Five news frames provided the theoretical framework. The findings show that CNN used responsibility and morality frames differently in its coverage of weather-related disasters in the three countries. This suggests that CNN might have different expectations about audiences. In frame building, factors like audience expectations influence media frames. There were no differences in the economic consequences and human interest framing of weather-related disasters in the three countries. Conflict framing was not present in CNN coverage of weather-related disasters in any of the three countries. The study recommends that CNN in particular and news media in general provide more coverage and in-depth analysis on the audience so that they can have a deeper understanding of weather-related disaster issues.